Influence of Local Budget Revenues on Social and Economic Development of Regions - Tayirov Shohboz Ziyodulla ugli; Salahiddinov Jaloliddin Ulug’bek ugli (European Science Publishing, 2023)
The article describes the scientific and practical aspects of the formation of the revenue base of local budgets, ensuring the effectiveness of local budget revenues and expenses. Reasonable use of the economic potential of the regions, as well as the reasonable and effective use of local budget expenses, the possibilities of ensuring the stability of local budgets' incomes are substantiated. Based on the research, practical recommendations were developed.
Keywords: local budget; local budget revenues; local budget expenditures; local authorities; local taxes and fees; territories; regional economy.